Upregulation of 15-Hydroxyprostaglandin Dehydrogenase by Celecoxib to Reduce Pain After Laparoendoscopic Single-Site Surgery (POPCORN Trial): A Randomized Controlled Trial - Kyung Hee Han; Sunwoo Park; Seungmee Lee; Jiyeon Ham; Whasun Lim; Gwonhwa Song; Hee Seung Kim (Biomedicines)
Background: Peritoneal stretching from CO2 insufflation is a primary mechanism of pain associated with laparoscopy. Cyclooxygenase-2 inhibitors are promising anti-inflammatory and analgesic agents. This study aimed to evaluate the effect of celecoxib on postoperative pain reduction and associated changes in peritoneal gene expression after laparoendoscopic single-site (LESS) surgery for benign gynecologic disease. Methods: In this randomized, double-blind, placebo-controlled pilot study, 70 patients were randomly assigned to receive either celecoxib or placebo (400 mg) 40 min before surgery. Peritoneal tissues were collected before and after CO2 insufflation. We analyzed changes in expressions of prostaglandin I2 synthase, prostaglandin E synthase (PTGES), PTGES3, aldo-keto reductase family 1 member C1, and 15-hydroxyprostaglandin dehydrogenase (HPGD). Numeric Rating Scale (NRS) pain scores were also compared between groups. Results: A total of 62 patients completed the study: 30 in the celecoxib group and 32 in the placebo group. The mean CO2 exposure time was 60.4 min. In a quantitative real-time polymerase chain reaction analysis, HPGD mRNA expression significantly increased after surgery in patients exposed to CO2 for more than 60 min. Patients treated with celecoxib showed a significantly higher rate of grade 3 expression (83.3% vs. 37.5%; p = 0.01) and a level 2 increase in HPGD expression on in situ hybridization (58.3% vs. 12.5%; p = 0.01), despite no significant difference on immunohistochemistry. Moreover, celecoxib effectively reduced NRS pain scores compared to placebo. Conclusions: In this pilot study, celecoxib appeared to reduce postoperative pain and was associated with increased HPGD mRNA expression in the peritoneal tissue of patients with prolonged CO2 exposure during LESS surgery. These exploratory findings warrant confirmation in larger trials with functional validation of HPGD expression (ClinicalTrials.gov, NCT03391570).